P244 A quality improvement project to optimise multidisciplinary team communication about unplanned admissions of clinical trial patients. (12th November 2019) - Dobra, R; Huband, K; Madge, S; Simmonds, NJ; Davies, JC
Abstract : Background: This is a hugely exciting time for Cystic Fibrosis (CF) research. There are more than 100 drugs in development offering substantial hope for improved health and life-expectancy. Clinical trial participants are asked to inform the trials team promptly of unplanned hospital admissions. Failure to do so results in delayed awareness and reporting of serious adverse events. Awareness on the part of the admitting clinical team would provide a safety net to speed up communication, improve patient safety and facilitate timely completion of regulatory paperwork. We aimed to assess and improve awareness within the MDT of the importance of these issues Methods: Questionnaires were distributed in handover and teaching sessions over two weeks in Feb 2018 to adult/paediatric ward nurses, CF clinical nurse specialists and ward doctors. These were used along with an MDT meeting to identify interventions to be implemented. Questionnaires were redistributed in August 2018 at similar opportunities. Interventions: Talks at educational MDT forums Names of trial patients/team contacts added to ward handover lists Trial participation flagged within all clinic correspondence Results: Post-intervention, there were significant improvements in the proportions of staff demonstrating awareness of procedures (Table). From February 2017 to January 2018 there was a median (range) of 18 (2–93) days before the trials team were made aware of 8 admissions compared with 2 (1–4) days (5 admissions) in February 2018 to January 2019 (p<0.001). Conclusion: Post intervention, the median number of days to trial team awareness of admissions reduced. There was a significant increase in the number of clinical staff who knew to inform the trials team of admissions and how to contact them, but still an inadequate proportion of staff asking about trial participation proactively. We will add a reminder to the admission/clerking proforma and clinic checklist and continue to highlight this message as it is an unmet educational need. We will reassess in one year to establish if improvements are sustained and aim to extend our work to improve communication and integration across multiple aspects of trial delivery. We suggest the principles could be relevant to other specialities conducting clinical trials.